2013
DOI: 10.1155/2013/406375
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Sparing Mastectomy with Immediate Breast and Nipple Reconstruction: A New Technique of Nipple Reconstruction

Abstract: Background. Most women with breast cancer today can be managed with breast conservation; however, some women still require mastectomy for treatment of their disease. Skin-sparing mastectomy (SSM) with immediate reconstruction has emerged as a favorable option for many of these patients. The authors combined the SSM technique with the preservation of a small part of the areola with immediate nipple together with with breast reconstruction. Methods. In an 8-year-period 155 female patients (age: 20–52 years old; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Quantitative synthesis included 37 studies 4,8,9,11,13,19,[21][22][23][24][25][26][27][28][29][30][39][40][41][42][43][44][45][46][47][50][51][52]56,58,59,[62][63][64][65]67,68 on autologous PMBR (Figs. 2A-E; Table S3a) and 28 studies 20,[31][32][33][34][35][36][37][38][41][42][43][46]…”
Section: Search Results and Synthesis Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative synthesis included 37 studies 4,8,9,11,13,19,[21][22][23][24][25][26][27][28][29][30][39][40][41][42][43][44][45][46][47][50][51][52]56,58,59,[62][63][64][65]67,68 on autologous PMBR (Figs. 2A-E; Table S3a) and 28 studies 20,[31][32][33][34][35][36][37][38][41][42][43][46]…”
Section: Search Results and Synthesis Of Evidencementioning
confidence: 99%
“…In total, 22 studies [31][32][33][34][35][36][37][38]42,[47][48][49]54,55,57,[59][60][61]64,[66][67][68] reported local recurrence after immediate implant-based post-mastectomy breast reconstruction (I-IBR) (Fig. 3A, I 2 = 42.1% [95% CI, 3.8%-65.1%]).…”
Section: Immediate Versus Delayed Implant-based Pmbrmentioning
confidence: 99%
“…Nipple-sparing mastectomy (NSM) is normally defined as SSM along with preservation of the nipple-areolar complex. 2 SSM is usually described as the procedure of mastectomy, either simple or modified radical, with minimal skin excision. SSM involves excision of the whole of the breast tissue including the nipple-areolar complex while sparing or preserving the breast skin envelope.…”
Section: Total Single-stage Breast Reconstruction With Free Nipple Grafts Using the Salvage Of Parts Conceptmentioning
confidence: 99%
“…Serra et al 2 recently demonstrated extensive ductal intraepithelial neoplasia or invasive breast cancer treated with areola SSM with immediate nipple and breast reconstruction is technically feasible and provide excellent cosmetic results. If we can fully reconstruct breasts in one stage, there is significant benefit.…”
Section: Total Single-stage Breast Reconstruction With Free Nipple Grafts Using the Salvage Of Parts Conceptmentioning
confidence: 99%
“…pioneered. These techniques include: skin-sparing mastectomy (SSM) where the breast tissue and the nipple areolar complex (NAC) are removed but the skin overlying the breast is preserved, and the nipple sparing mastectomy (NSM), where the skin and NAC are preserved [3,[5][6][7][8] . Preserving the skin in an SSM and the preservation of the NAC in the NSM results in better cosmesis, improved patient satisfaction, and quality of life [3,5,8,9] .…”
mentioning
confidence: 99%